Sermaye şirketlerinde hisse senetlerinin değerlemesi ve Türkiye’den halka açık bir şirkete yönelik uygulama ve raporlama - Yürüdü, Ali (My University, 2005)
In recent years, because of the development of the capital market the firms which want to submit their shares in stock market and the investors who want to purchase these shares have the desire for knowledge of the shares' current market value which lead the subject of valuation become important. The subject of valuation takes place in priority in finance literature and increasingly gains ground. The equity capital valuation of a firm consists of the estimation of the shares' current market value. It should not be thought that the values calculated in this field represent the exact values. However, it is possible that the values existing in the negotiation are the most closest values. The subject of this thesis is the explanation of the methods enforced in finding the current market value of the shares. For this purpose; In the first section of the thesis (introduction); the general concepts of valuation are emphasized. In the second section of the thesis; the definition of the firm's valuation and the aims of valuation are examined. In the third section of the thesis, the methods and approaches of valuation are examined. In the fourth section of the thesis, the special conditions encountered in valuation and the rearrangement of the financial statements before valuation are examined. In the fifth section of the thesis, the ratios employed in the share valuation are stressed. In the sixth section of the thesis, the subject of valuation is observed in the implementation. In the conclusion section of the thesis, the conclusion attained up to this point is explained. The firm valuation is generally based on the estimation of the market value of shares. However, it should not be thought that estimated value represents an unique and exact values. The investors are interested in the financial structures, the sale of assets,and the benefits of final sale of present shares. Thus, the investors will analyze the earnings, income, cash flows, shares of profit, book values and maybe other main contributors factors in decision making. Some of them will provide more detail knowledge relatively the others. The sector of this business changes according to the business type and the enforcement of the business. However, the investors should determine which one of them is important. Bu tez çalışmasının konusu öncelikle, bilinen ve genel kabul görmüş değerleme yaklaşım ve yöntemlerinin incelenmesidir. Buna ilave olarak halka açık bir anonim şirketinin hisse senedi değeri, indirgenmiş devamlı nakit akımı yöntemi (gelir yaklaşımı), karşılaştırmalı denk şirketler yöntemi (piyasa kıyaslama yaklaşımı) ve tasfiye yöntemine (aktif bazlı yaklaşım) göre hesaplanmıştır. Bu tez çalışması beş bölümden oluşmaktadır. Birinci bölümde, başlıca ve genel kabul görmüş değer kavramları incelenmek suretiyle, hisse senedi değerleme konusuna giriş yapılmıştır. İkinci bölümde öncelikle hisse senedi değerlemesi tanımı ve amaçlarına yer verilmektedir. Bunu takiben, hisse senedi değerleme yaklaşım ve yöntemleri açıklanmaktadır. Üçüncü bölümde ilk olarak hisse senedi değerlemesinde karşılaşılan özel durumlar yer almaktadır. Buna ilave olarak, değerleme çalışmasına başlamadan önce, mali tabloların analize hazır hale getirilmesi amacıyla yeniden oluşturulması için gerekli olan düzeltmeler incelenmektedir. Dördüncü bölümde, hisse senedi değerlemesine ışık tutmak amacıyla analiz edilmeleri gereken belli başlı finansal rasyolar yer almaktadır. Beşinci bölümde öncelikle, halka açık bir anonim şirketinin hisse senedi değeri üç değişik değerleme yöntemi (indirgenmiş devamlı nakit akımı yöntemi, karşılaştırmalı denk şirketler yöntemi, tasfiye yöntemi) bazında ayrıntılı olarak hesaplanmaktadır. Bunu takiben de, söz konusu yöntemler ışığında bulunan farklı değerlerin karşılaştırılması ve birleştirilmesi suretiyle, şirketin hisse değeri olarak tek bir değerde mutabık kalınacağı görülmektedir. Birden fazla yönteme göre değer bulmak, yukarıda bahsedilen karşılaştırmayı yapabilmek açısından fayda sağlamaktadır. Diğer bir yandan, değerleme çalışmasında önemli olanın fazla yöntem kullanmaktan çok, şirket için en uygun yöntemi bulmak olduğu da unutulmamalıdır. Bu sebeple, söz konusu yöntemlere göre bulunan değerlerin ortalamasının, şirketin hisse değerini yansıttığı sonucuna varılmıştır.
Keywords: Hisse Senetleri